KINETIC STUDIES OF THE FISCHER TROPSCH SYNTHESIS OVER CO-K/?-AL2O3 CATALYST - Fadhli
The world's demand for new energy sources is increasing, especially in liquid fuels that are still the main energy source. Fuel synthesis technology from various sources has been developed, one of them is Fischer Tropsch technology. The Fischer Tropsch technology reacts CO and H2 (syngas) on the surface of the solid catalyst through a polymerization reaction resulting in a hydrocarbon compound of varying chain length. The most widely used catalyst for a Fischer Tropsch reaction is a supported cobalt catalyst. The result of catalyst test at temperature condition 200oC and total pressure of 20 bar showed good activity of Co-K/?-Al2O3 catalyst with CO and H2 conversion are 96,48% and 81,83% and selectivity to C5+ 79,40%. Knowledge of the Fischer Tropsch reaction kinetics has become an important key in the application of Fischer Tropsch technology on an industrial scale, especially in reactor design and determination of operating conditions. Testing the kinetics and estimation of the kinetics parameters of the Fischer Tropsch reaction on Co-K /?-Al2O3 catalysts were carried out with a series of variations in reaction temperature and syngas flow rate. The kinetics model of the Fischer Tropsch reaction is explained by empirical and mechanistic kinetics models. The empirical kinetic model is based on the power law equation. The activation energy for the power law model is obtained at 31 kJ/mol. The reaction order obtained is -2 for CO and 0,75 for H2 with an error value less than 3% for each reaction temperature. The mechanistic kinetics model is derived from the study of the mechanism of the Fischer Tropsch reaction by assuming one of the steps in the reaction mechanism as the controlling step. The kinetic model through the associative path successfully estimates the kinetic and thermodynamic parameters of the Fischer Tropsch reaction with the smallest error value, the activation energy values obtained are 81,4 kJ/mol and the enthalpy of CO and H2 adsorption reactions on the catalyst surface is 21,3 kJ/mol and 77 kJ/mol. The development of kinetics models through dissociative pathways is done to get a more complex kinetics model. The parameters obtained in the dissociative kinetics model are a combination of several kinetic and thermodynamic parameters so that they cannot be specified. Dissociative kinetics models provide an explanation of the phenomena that occur during the Fischer Tropsch reaction more clearly.